INFLUENCE OF PHYTASE ENZYME ON GROWTH PERFORMANCE AND SURVIVAL RATE CHALLENGED WITH SAPROLEGNIA SPP. IN COMMON CARP - & Mustafa, Fadhal (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study was aimed to investigate the effect of phytase as a feed additive on growth performance and survival rate against Saprolegnia spp.in common carp, Cyprinus carpio L. A total of 120 C. Carpio (initial mass 20.05-20.35g) were randomly stocked into six treatments in duplicate (10 fish/tank) as follows: T1, T2, and T3 were fed the basal diet supplemented with phytase at 1000, 2000, and 4000 IU/Kg diet respectively, while T4 were fed on basal diet plus β-glugan at a concentration of 8.5 g/kg as well as the control group was fed basal diet without any addition of phytase. Results showed after 60 days of feeding period, that the addition of phytase enzyme was significantly (p